PENGARUH KEPUTUSAN INVESTASI DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DIMEDIASI DAN DIMODERASI PROFITABILITAS (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2013 – 2016) - Patricia Dhiana Paramita; Arditya Dian Andika (Universitas Pandanaran, 2021)
Companies in making decisions to invest must carefully consider various aspects so that in the future the prospects for the benefits will be maximized, on the other hand, in making dividend policies, the amount must also increase in the hope that it will have a positive impact on company value in the eyes of investors. The formulation of the problem in this study is how management's efforts to improve investment decisions and make dividend policies that have a positive impact on company value are mediated and moderated by profitability. The research objectives to be achieved are to determine the effect of investment decisions and dividend policy partially on profitability and firm value, to determine the effect of profitability on firm value and to determine whether profitability mediates and derives the effect of investment decisions and dividend policy partially on firm value.The population in this research were 114 manufacturing companies listed on the IDX in 2013 - 2016. The sample was determined by using purposive sampling method, so that the number of samples taken was 30 companies. The data analysis technique used is multiple linear regression, path analysis and Moderated Regression Analysis (MRA). Based on the results of data analysis, it can be seen that investment decisions and dividend policies partially have a positive and significant effect on company profitability and value, profitability has a positive and significant effect on firm value and profitability mediates and moderates the effect of investment decisions and dividend policy partially on firm value. Keywords: investment decisions, dididen policies, profitability and firm value